A Survey on Assessment of the Prevailing School Fees for Private Secondary Schools in Tanzania - Nyahende, Veronica R.; Cosmas, Benedicto C. (International Journal of Learning, Teaching and Educational Research, 2016)
Higher Education Students’ Loans Board (HESLB) has been using secondary school fees as a key component in determining neediness for loan applicants at Higher Education (HE). Such fees are used as proxy indicator of the ability of parents/guardians to meet the costs of higher education in complementing the Government effort. This survey was conducted to assess the actual schools fees charged per student in the private secondary schools. The survey was geared towards achieving the following objectives (i) to examine the amount of school fees charged per student by private secondary schools (ii) to assess the components of school fees for private secondary schools (iii) to determine schools with special scholarship/grants programmes and the criteria thereof. This survey was conducted in all regions countrywide after being clustered into 5 groups (5 zones), Dodoma, Mwanza, Zanzibar, Arusha and Mbeya. Private secondary schools were visited in which data were collected from 260 respondents. Data collected were analyzed using Excel and Statistical Package for Social Science (SPSS). Results were summarized in Tables, Figures and in Narrative form. The study concluded that currently private secondary schools are charging school fees at a range of Tshs. 500,000 and Tshs.1,000,000. It was further concluded that the components of the school fees as shown by most of the private secondary schools visited includes examination fees (Mock, National Examination Council-NECTA), Caution money, Admission fees, Identity cards, Registration fees, Medical fees and Boarding fees. It was further concluded that selection of students for financial support is basing on the orphanage status, family background and academic performance of the students. It was recommended that the Government should set standard of the amount of school fees to be charged in all private secondary schools as it is for the Public secondary schools. It was further recommended that Private secondary schools should ensure that components of school fees which do not directly relate to the learning process are treated separately and not as part of school fees for example inspection/ audit fees. It is also recommended that the Government should set rules to ensure that there is a specific number of students to be financially supported by any established private secondary school hence adequate participation of each private secondary school in provisions of scholarships and/or grants.